The Possibilities of Tertiary Crime Prevention - Nikolić, Zlatko (Zbornik Instituta za kriminološka i sociološka istraživanja, 2009)
Tertiary crime prevention, as it is to be seen in the following succeeding text, means a treatment of particular individuals – crime offenders, already sanctioned by some of the possible penalties for certain crimes. This, furthermore, is the oldest approach to the treatment of offenders, also known as penal reaction, but since the late 18th and early 19th century, it has been given a form of prevention, that is, an attempt to affect crime offenders as a measure of resocialization. What are the possibilities and which conditions could make this method effective at least up to a certain point, is to be a subject of the following analysis.